A review of ex vivo placental perfusion models: an underutilized but promising method to study maternal-fetal interactions. (12th December 2022) - Calis, Pinar; Vojtech, Lucia; Hladik, Florian; Gravett, Michael G.
Abstract: Studying the placenta can provide information about the mechanistic pathways of pregnancy disease. However, analyzing placental tissues and manipulating placental function in real-time during pregnancy is not feasible. The ex vivo placental perfusion model allows observing important aspects of the physiology and pathology of the placenta, while maintaining its viability and functional integrity, and without causing harm to mother or fetus. In this review, we describe and compare setups for this technically complex model and summarize outcomes from various published studies. We hope that our review will encourage wider use of ex vivo placental perfusion, which in turn would generate more knowledge to improve pregnancy outcomes.